PELAKSANAKAN FUNGSI PENGAWASAN DISTRIBUSI BAHAN BAKAR MINYAK DI KOTA PONTIANAK - Jani E.21109045 (FISIP Universitas Tanjungpura, 2013)
One of role on duty mining and West Kalimantan Province Energy, are perform observation to Common Bunkering Station (SPBU) in order to anticipate its happening Fuels Oil Material (BBM) distribution, notably BBM gets to subsidise Pontianak City. To the effect another observation, that 25 SPBU at Pontianak City always notices aspect Safety, Job health and Environmentally (K3LL). Executed things as subjective that observation, covering checking about SPBU SOP equipment, performing K3LL SPBU.Reality points out that supervisory role by on duty mining and West Kalimantan of Province Energy, insufficiently been performed necessarily, since: (1) Officer stills performing deep frails orders, so mingling problem, conglomeration and also BBM wild and buy pickings gets to subsidise in large quantities via tank modification as indication of collusion among officer/SPBU operator with society interrupts me consumer am still get to be found; (2) Cost factor or budget allocation as subjective as observation to each SPBU relates BBM distribution, and ensues on its minim supervisory intensity that necessarily gets to be done 3 deep times one year, enforced been done once deep one year; and (3) Resources weakness factor supervisor officers amounts most heavy enough count and requires accuracy and time that adequately to base, and seeing directly SPBU condition until to investigative phase. Key word: Distribution BBM gets to subsidise, Observation and SPBU.